The Aesthetic Religious Symbol of The First Abbasid Era : Bashar Ibn Barad – Ibn AL Rumi ,AS Models - Hussein Oleiwi, Najlaa Abdul; Farhan Hussein, Mohammed (Opción, 2019)
The symbol is a technical tool that receives the attention of scholars to its literary and heritage status and its significance, which carries in its machines the aesthetic value that expresses its symbol. The symbol has roots since the first date. The philosophers of the Greeks and Arabs had a pause with them in their manuscripts and scientific, because of its codes on it by people, as Car- ries many meanings and indications that make the recipient in a state of alert and emotion with these symbols to be through the images and values that can guide them to what the poet and writer A, be a mask hiding behind the author.